Rapid-curing high-interface bonding strength coating material for cement pavement and preparation method of rapid-curing high-interface bonding strength coating material

By using a specially made cement road surface on the airport cement road surface, the problems of slow curing speed and insufficient interface bonding in the existing technology are solved, and efficient and safe repair results are achieved And good anti-freeze-thaw performance, suitable for rapid repair and improving the safety of airport road surface operation.

CN119263755APending Publication Date: 2025-01-07CIVIL AVIATION UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411519280.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing airport cement road surface repair materials cannot meet the requirements of rapid repair and safe operation due to their slow curing speed and insufficient interface adhesion. Especially in complex climate environments such as strong freeze-thaw, there are road surface diseases and external threats.

Method used

Provide a fast curing high-interface bonding strength coating material for cement pavement surface, made of a mixture of solid components and liquid components at a weight ratio of 2:1. The solid components include silicate cement and sulfur aluminate cement , quartz sand, etc., the liquid components include aqueous epoxy resin and aqueous epoxy curing agent, which are prepared by specific proportions and stirring steps to form a coating material with high interfacial bonding strength.

Benefits of technology

The material cured within 30 minutes, the interface bonding strength reached 0.8MPa in 3 hours, 1MPa in 24 hours, and 1.2MPa in 7 days, significantly improving the bonding force between the restoration layer and the old concrete, ensuring construction efficiency and freeze-thaw resistance Performance, suitable for mechanized construction, the repair efficiency is increased by 10-20 times, extending the durability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263755A_ABST
    Figure CN119263755A_ABST
Patent Text Reader

Abstract

The invention relates to a cement pavement rapid curing high interface bonding strength coating material and a preparation method thereof. The material is prepared by mixing a solid component and a liquid component, the solid component is prepared by mixing Portland cement, sulphoaluminate cement, quartz sand, alpha semi-hydrated gypsum, silica fume, silane and rubber powder; the liquid component is prepared by mixing water-borne epoxy resin, a water-borne epoxy curing agent and water. The coating material has the advantages that the coating material can be cured within 30 min to form a coating, the interface bonding strength reaches 0.8 MPa after curing is conducted for 3 h, the interface bonding strength reaches 1 MPa after curing is conducted for 24 h, and therefore it is ensured that a repairing layer and old concrete are tightly combined, and the repairing layer is effectively prevented from falling off. Construction is convenient and efficient, and the repairing efficiency can be improved by 10-20 times. The coating has good freeze-thaw resistance, and the durability of the coating can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rapid repair of cement pavement at an airport, and in particular relates to a rapid-curing high-interface bonding strength coating material for a cement pavement and a preparation method thereof. Background Art

[0002] With the rapid development of the aviation industry, large transport aircraft have gradually been put into use. In addition, the complex climate environment such as strong freeze-thaw and extremely low temperature has put forward higher requirements on the performance of airport cement pavements. According to research and analysis, the surface diseases of most airport pavements are prominent. However, the existing repair materials are usually unable to meet the requirements of non-stop construction and repair due to their slow curing speed. In addition, due to the lack of interface adhesion, the repair materials are prone to produce pavement foreign objects (FOD), which threatens the safety of pavement operation. In this context, there is an urgent need to develop a fast-curing high interface bonding strength coating material to solve these problems. Summary of the invention

[0003] In order to solve the above problems, the object of the present invention is to provide a cement pavement fast-curing high interface bonding strength coating material and a preparation method.

[0004] In order to achieve the above-mentioned purpose, the cement pavement fast-curing high interface bonding strength coating material provided by the present invention is prepared by mixing a solid component and a liquid component in a weight ratio of 2:1; wherein the solid component is prepared by mixing silicate cement, sulphoaluminate cement, quartz sand, α-hemihydrate gypsum, silica fume, silane and rubber powder in a weight ratio of 15-20:21-24:15-18:2-5:3-5:0.33-0.43:0.55-0.72; the liquid component is prepared by mixing a water-based epoxy resin, a water-based epoxy curing agent and water, wherein the water-based epoxy resin and the water-based epoxy curing agent are mixed in a weight ratio of 2:1 to form a water-based epoxy mixture, and the water-based epoxy mixture is then mixed with water in a weight ratio of 1:1.5 to form a liquid component.

[0005] The silicate cement adopts 525 silicate cement; the sulphoaluminate cement adopts 525 or 725 sulphoaluminate cement; the mesh number of quartz sand is above 100 mesh; the mesh number of α-hemihydrate gypsum is 200-400 mesh; the mesh number of silica fume is 1000-2000 mesh; silane and rubber powder adopt commercial products; the epoxy equivalent of water-based epoxy resin is 400-800G / EQ, and the solid content is 47-53%; the active ammonia equivalent of water-based epoxy curing agent is 200-320, and the solid content is 42-46%.

[0006] The method for preparing the cement pavement fast curing high interface bonding strength coating material comprises the following steps performed in sequence:

[0007] 1) Weigh silicate cement, sulphoaluminate cement, quartz sand, α-hemihydrate gypsum, silica fume, silane and rubber powder according to the above proportions, mix and slowly stir for 30 seconds until completely uniform to prepare a solid component;

[0008] 2) Weigh the waterborne epoxy resin and the waterborne epoxy curing agent according to the above ratio, mix them, stir slowly for 30 seconds, and then stir quickly for 60 seconds until they are completely uniform, to prepare a waterborne epoxy mixture;

[0009] 3) adding a corresponding proportion of water to the above aqueous epoxy mixture and rapidly stirring for 120 seconds to prepare a liquid component;

[0010] 4) Slowly add the solid component to the liquid component according to the above ratio, first slowly stir for 30 seconds, then quickly stir for 180 seconds, and finally make a slurry-like cement pavement fast-curing high interface bonding strength coating material.

[0011] Compared with the prior art, the present invention has the following beneficial effects:

[0012] (1) The fast-curing high interface bonding strength coating material for cement pavement provided by the present invention can be cured within 30 minutes to form a coating. The interface bonding strength reaches 0.8 MPa after 3 hours of curing, 1 MPa after 24 hours, and 1.2 MPa after 7 days. Therefore, it has significant advantages over existing thin layer repair materials, thereby ensuring a close bond between the repair layer and the old concrete, and effectively preventing the problem of the repair layer falling off.

[0013] (2) The cement pavement fast-curing high interface bonding strength coating material provided by the present invention has the characteristics of convenient and efficient construction, with a fluidity of 100-120 mm, which can effectively meet the requirements of mechanized construction spraying and can improve the repair efficiency by 10-20 times without increasing costs.

[0014] (3) The coating made of cement pavement fast-curing high interface bonding strength coating material has good freeze-thaw resistance, which helps to extend the durability of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 (a) and (b) are comparison diagrams of the cement pavement fast-curing high interface bonding strength coating material provided by the present invention before and after curing on the concrete base surface.

[0016] Figure 2 These are the pull-out strength test results of the cement pavement fast-curing high interface bonding strength coating material provided by the present invention at different curing times.

[0017] Figure 3(a) and (b) are respectively comparison diagrams of concrete samples before and after freeze-thaw coating with the cement pavement fast-curing high interface bonding strength coating material provided by the present invention. DETAILED DESCRIPTION

[0018] The present invention is further illustrated below through the description of specific implementation modes, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention.

[0019] The present invention is described in detail below with reference to specific embodiments.

[0020] Example 1

[0021] The cement pavement fast curing high interface bonding strength coating material provided in this embodiment is prepared by mixing solid components and liquid components in a weight ratio of 2:1; wherein the solid components are prepared by mixing 525 silicate cement, 525 sulphoaluminate cement, 120 mesh quartz sand, 200 mesh α semi-hydrated gypsum, 1000 mesh silica fume, silane and rubber powder in a weight ratio of 19g:21g:17g:5g:4g:0.34g:0.56g; the liquid components are prepared by mixing waterborne epoxy resin, waterborne epoxy curing agent and water in a weight ratio of 6.67g:3.33g:15g, wherein the epoxy equivalent of the waterborne epoxy resin is 400G / EQ, the solid content is 50%, and the active ammonia equivalent of the waterborne epoxy curing agent is 200, and the solid content is 44%. Silane, rubber powder, waterborne epoxy resin and waterborne epoxy curing agent are all commercially available products.

[0022] The method for preparing the cement pavement fast curing high interface bonding strength coating material comprises the following steps performed in sequence:

[0023] 1) Weigh 19 g of 525 silicate cement, 21 g of 525 sulphoaluminate cement, 17 g of 120 mesh quartz sand, 5 g of 200 mesh α-hemihydrate gypsum, 4 g of 1000 mesh silica fume, 0.34 g of commercially available silane and 0.56 g of rubber powder, mix and slowly stir for 30 seconds until completely uniform to prepare a solid component;

[0024] 2) Weigh 6.67 g of waterborne epoxy resin and 3.33 g of waterborne epoxy curing agent, mix them, stir slowly for 30 seconds, and then stir rapidly for 60 seconds until they are completely uniform, to prepare a waterborne epoxy mixture;

[0025] 3) Add 15 g of water to the above aqueous epoxy mixture and stir rapidly for 120 seconds to prepare a liquid component;

[0026] 4) Slowly add the above solid component to the liquid component, the weight ratio of the solid component to the liquid component is 2:1, first slowly stir for 30 seconds, then quickly stir for 180 seconds, and finally make a slurry-like cement pavement fast-curing high interface bonding strength coating material.

[0027] Example 2

[0028] The cement pavement fast curing high interface bonding strength coating material provided in this embodiment is prepared by mixing solid components and liquid components in a weight ratio of 2:1; wherein the solid components are prepared by mixing 525 silicate cement, 725 sulphoaluminate cement, 110 mesh quartz sand, 300 mesh α-hemihydrate gypsum, 1500 mesh silica fume, silane and rubber powder in a weight ratio of 15g:22g:15g:2g:3g:0.38g:0.62g; the liquid components are prepared by mixing waterborne epoxy resin, waterborne epoxy curing agent and water in a weight ratio of 6.67g:3.33g:15g, wherein the epoxy equivalent of the waterborne epoxy resin is 600G / EQ, the solid content is 48%, and the active ammonia equivalent of the waterborne epoxy curing agent is 280, and the solid content is 42%. Silane, rubber powder, waterborne epoxy resin and waterborne epoxy curing agent are all commercially available products.

[0029] The preparation method is the same as that of Example 1.

[0030] Example 3

[0031] The cement pavement fast curing high interface bonding strength coating material provided in this embodiment is prepared by mixing solid components and liquid components in a weight ratio of 2:1; wherein the solid components are prepared by mixing 525 silicate cement, 525 sulphoaluminate cement, 100 mesh quartz sand, 400 mesh α-hemihydrate gypsum, 2000 mesh silica fume, silane and rubber powder in a weight ratio of 20g:24g:18g:5g:5g:0.43g:0.70g; the liquid components are prepared by mixing waterborne epoxy resin, waterborne epoxy curing agent and water in a weight ratio of 6.67g:3.33g:15g, wherein the epoxy equivalent of the waterborne epoxy resin is 800G / EQ, the solid content is 50%, and the active ammonia equivalent of the waterborne epoxy curing agent is 300, and the solid content is 46%. Silane, rubber powder, waterborne epoxy resin and waterborne epoxy curing agent are all commercially available products.

[0032] The preparation method is the same as that of Example 1.

[0033] The cement pavement fast curing high interface bonding strength coating material provided in the above embodiment is applied to the concrete base surface to be repaired. After the cement pavement fast curing high interface bonding strength coating material solidifies, a uniform, dense and highly adhesive coating layer can be quickly formed on the concrete base surface as a repair layer. The comparison results before and after curing are shown in FIG. Figure 1 As shown in (a) and (b).

[0034] In order to verify the effect of the present invention, the applicant conducted the following experiments:

[0035] 1. Based on the mortar fluidity test, the workability of the cement pavement fast curing high interface bonding strength coating material prepared in the above embodiment is verified;

[0036] According to the standard "JCT985-2017 Cement-based Self-leveling Mortar for Floor", the mortar fluidity test was carried out. After testing, the fluidity value of the cement pavement fast-curing high interface bonding strength coating material prepared in the above embodiment was 120 mm. Under the premise of the standard "JCT985-2017 Cement-based Self-leveling Mortar for Floor", according to the working conditions, the mortar fluidity value should be greater than 90 mm. Therefore, this cement pavement fast-curing high interface bonding strength coating material can meet the requirements of large-scale spraying construction.

[0037] 2. The interface bonding strength, bonding flexural strength and freeze-thaw performance of concrete samples of the cement pavement fast curing high interface bonding strength coating material prepared by the above embodiment were evaluated:

[0038] ①Interface bonding strength

[0039] The cement pavement fast curing high interface bonding strength coating material prepared in the above embodiment is coated between the drawing block and the drawing substrate. After the cement pavement fast curing high interface bonding strength coating material solidifies into a coating, a cement pavement sample is prepared. The thickness is controlled at 6mm using a silicone template, and the curing time is controlled to 3h, 6h, 24h and 168h for subsequent tests. The LBY-VI type bonding strength pulling instrument (range 0-5000N) is used to perform a pulling test on the cement pavement sample prepared above at a fixed speed of 5mm / min at room temperature. The results are as follows: Figure 2 shown.

[0040] Depend on Figure 2 It can be seen that the interface bonding strength of the coating of the present invention reaches 0.8MPa after 3 hours of curing, the interface bonding strength reaches 1MPa after 24 hours, and the interface bonding strength still reaches 1.2MPa after 7 days. According to research, the interface bonding strength of the airport cement pavement of the existing pavement coating material for 24 hours is about 0.5MPa, which is much lower than the interface bonding strength of the airport cement pavement fast curing high interface bonding strength coating material provided by the present invention. It can be seen that the airport cement pavement using the airport cement pavement fast curing high interface bonding strength coating material provided by the present invention has excellent interface bonding strength, and the interface bonding strength of the coating for 24 hours reaches 1MPa, which has the characteristics of rapid curing and meets the requirements of airport pavement.

[0041] ② Bond flexural strength

[0042] A standard test piece of 40mm×40mm×160mm was cut from the center using a cutting machine, half of which was placed in a triple steel mold, and the other half was cast with the coating material of the present invention. After curing for 7 days according to the cement test piece curing standard, it was placed in a HYAZ-300 constant pressure compression and flexural testing machine, and a load speed of 0.05MPa / s was applied at room temperature until the test piece broke. The test results show that the bonding flexural strength of the coating of the present invention reaches 1.31MPa, which is significantly better than the same type of coating on the market.

[0043] ③ Freeze-thaw performance

[0044] First, five surfaces of the cement mortar test block were sealed with epoxy glue and left to dry at room temperature for two days until the epoxy glue was completely solidified. Then, the coating material of the present invention was applied to the side of the sample without sealant, and the coating was applied twice, with an interval of 12 hours between the two coatings, and then left to stand at room temperature for 7 days.

[0045] After the freeze-thaw test specimens were treated, the freeze-thaw resistance of the coating of the present invention was evaluated according to the freeze-thaw resistance test method of cement concrete in "JTG3420-2020 Test Code for Cement and Cement Concrete in Highway Engineering". The freeze-thaw test results are shown in Table 1.

[0046] Table 1. Freeze-thaw test results

[0047]

[0048] It can be seen that after the cement specimen is coated, the mass and elastic modulus loss under freeze-thaw conditions are reduced, proving that the coating of the present invention has an improving effect on the freeze-thaw resistance of the pavement. Figure 3 As shown in (a) and (b).

[0049] In summary, the coating material of the present invention has good fluidity, is easy to spray, has high construction efficiency, has high interface bonding strength, and has a short curing time, and is suitable for large-scale pavement construction. In addition, the prepared coating has good anti-freezing and thawing properties, which can meet the requirements of some airports for pavement anti-freezing properties, and is suitable for repairing airport cement pavements to meet market demand.

Claims

1. A cement pavement fast curing high interface bonding strength coating material, characterized by: The cement pavement fast-curing high interface bonding strength coating material is prepared by mixing a solid component and a liquid component in a weight ratio of 2:1; wherein the solid component is prepared by mixing silicate cement, sulphoaluminate cement, quartz sand, α-hemihydrate gypsum, silica fume, silane and rubber powder in a weight ratio of 15-20:21-24:15-18:2-5:3-5:0.33-0.43:0.55-0.72; the liquid component is prepared by mixing a water-based epoxy resin, a water-based epoxy curing agent and water, wherein the water-based epoxy resin and the water-based epoxy curing agent are mixed in a weight ratio of 2:1 to form a water-based epoxy mixture, and the water-based epoxy mixture is then mixed with water in a weight ratio of 1:1.5 to form a liquid component.

2. The cement pavement fast curing high interface bonding strength coating material according to claim 1, characterized in that: The silicate cement adopts 525 silicate cement; the sulphoaluminate cement adopts 525 or 725 sulphoaluminate cement; the mesh number of quartz sand is above 100 mesh; the mesh number of α-hemihydrate gypsum is 200-400 mesh; the mesh number of silica fume is 1000-2000 mesh; silane and rubber powder adopt commercial products; the epoxy equivalent of water-based epoxy resin is 400-800G / EQ, and the solid content is 47-53%; the active ammonia equivalent of water-based epoxy curing agent is 200-320, and the solid content is 42-46%.

3. A method for preparing a cement pavement fast curing high interface bonding strength coating material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps performed in sequence: 1) Weigh silicate cement, sulphoaluminate cement, quartz sand, α-hemihydrate gypsum, silica fume, silane and rubber powder according to the above proportions, mix and slowly stir for 30 seconds until completely uniform to prepare a solid component; 2) Weigh the waterborne epoxy resin and the waterborne epoxy curing agent according to the above ratio, mix them, stir slowly for 30 seconds, and then stir quickly for 60 seconds until they are completely uniform, to prepare a waterborne epoxy mixture; 3) adding a corresponding proportion of water to the above aqueous epoxy mixture and rapidly stirring for 120 seconds to prepare a liquid component; 4) Slowly add the solid component to the liquid component according to the above ratio, first slowly stir for 30 seconds, then quickly stir for 180 seconds, and finally make a slurry-like cement pavement fast-curing high interface bonding strength coating material.